Respuestas
Respuesta dada por:
27
Factorizar.
Caso.
Diferencia de Cubos.
a³ - b³ = (a - b)(a² + ab + b²)
y³ - 1 =
y³ - 1³ =
(y - 1)(y² + y + 1)
Respuesta.
y³ - 1 =(y - 1)(y² + y + 1)
Caso.
Diferencia de Cubos.
a³ - b³ = (a - b)(a² + ab + b²)
y³ - 1 =
y³ - 1³ =
(y - 1)(y² + y + 1)
Respuesta.
y³ - 1 =(y - 1)(y² + y + 1)
Respuesta dada por:
2
Respuesta:
mas umenos asi como entiendo yo...
Adjuntos:
![](https://es-static.z-dn.net/files/ddb/29dd26106aedeb1e67fae77984d5615a.jpg)
Preguntas similares
hace 9 años
hace 9 años
hace 10 años
hace 10 años